Metode Kritis Al-Shawkânî dalam Kitab Nayl Al-Awţâr - Zainuddin MZ, Zainuddin (ISLAMICA: Jurnal Studi Keislaman, 2009)
Of the many sources for the study of HadÃ®th and the science of law and legal arrangements (al-ahkÃ¢m wa al-mawÃ¢â id), KitÃ¢b MuntaqÃ¢ al-AkhbÃ¢r by Majd al-DÃ®n Abd al-SalÃ¢m bin Abdullah bin QÃ¢sim better known as Ibn Taymiyyah (d. 652 H) is one of the most important. This book has been commented by al-ShawkÃ¢nÃ® in a book called Nayl al-AwÅ£Ã¢r where he employs the following methods. First, elaborating and commenting not of all hadiths but some them in each chapter of the book. Second, describing the narrators of the hadÃ®ths, their quality and personality. Third, providing the literal meaning of the hadÃ®ths he commented. Fourth, explaining the grammatical position of the vocabularies of the hadÃ®th. Fifth, highlighting the use and benefit of the hadÃ®th. Sixth, explaining the views of various ulama on a hadith. Seventh, extrapolating the legal rules of the hadÃ®th using the dictums of the uÅÃ»l al-fiqh. This paper is designed to discuss this. It holds that in providing the commentary of the hadith, al-ShawkÃ¢nÃ® begins with the issue of how it was narrated (takhrÃ®j), and ends up with extrapolating rules that may be learnt from it. The paper also believes that al-ShawkÃ¢nÃ® is an objective scholar, who worked in the elaboration and commentary of the hadÃ®ths just for the sake of knowledge. The fact that he often offers a commentary against the legal position of his own school of thought indicates that al-ShawkÃ¢nÃ® a person of academic integrity. The methods that he employs and the spirit behind his determination to provide commentary, all point to one thing of particular importance, that al-ShawkÃ¢nÃ® is immune of fanaticism and imitation.